Patient-reported health outcomes of SARS-CoV-2–tested patients presenting to emergency departments: a propensity score–matched prospective cohort study. (February 2023) - Bola, R.; Sutherland, J.; Murphy, R.A.; Leeies, M.; Grant, L.; Hayward, J.; Archambault, P.; Graves, L.; Rose, T.; Hohl, C.
Abstract: Objective: This study aimed to compare the long-term physical and mental health outcomes of matched severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-positive and SARS-CoV-2–negative patients controlling for seasonal effects. Study design: This was a retrospective cohort study. Methods: This study enrolled patients presenting to emergency departments participating in the Canadian COVID-19 Emergency Department Rapid Response Network. We enrolled consecutive eligible consenting patients who presented between March 1, 2020, and July 14, 2021, and were tested for SARS-CoV-2. Research assistants randomly selected four site and date-matched SARS-CoV-2–negative controls for every SARS-CoV-2–positive patient and interviewed them at least 30 days after discharge. We used propensity scores to match patients by baseline characteristics and used linear regression to compare Veterans RAND 12-item physical health component score (PCS) and mental health component scores (MCS), with higher scores indicating better self-reported health. Results: We included 1170 SARS-CoV-2–positive patients and 3716 test-negative controls. The adjusted mean difference for PCS was 0.50 (95% confidence interval [CI]: -0.36, 1.36) and -1.01 (95% CI: -1.91, -0.11) for MCS. Severe disease was strongly associated with worse PCS (β = −7.4; 95% CI: -9.8, -5.1), whereas prior mental health illness was strongly associated with worse MCS (β = −5.4; 95% CI: -6.3, -4.5). Conclusion: Physical health, assessed by PCS, was similar between matched SARS-CoV-2–positive and SARS-CoV-2–negative patients, whereas mental health, assessed by MCS, was worse during a time when the public experienced barriers to care. These results may inform the development and prioritization of support programs for patients.